Vertentes em tempos de modernização: o despertar de uma cidade nas décadas de 1920-1970. - Almeida , Edjane Chagas de (2024)
This work aims to study the transformations that occurred in the city of Vertentes, located in the Agreste region of Pernambuco, approximately 150 km from Recife, during the advent of modernity. Using sources such as photographs, newspapers and municipal laws. Due to the lack of sources and specific studies on the historical trajectory of Vertentes, much existing information is fragmented, leaving the local population without consistent knowledge of its history. Given this context, this work seeks to contribute to a greater understanding of social and cultural transformations and urban events that occurred in Vertentes during the 1920s-1970s. The result of this report is an ebook, containing facts, information and images from that period.